Potential of silk proteins in cosmetics - Qadir, Jasmeena; Islam, Tajamul (Journal of Scientific Agriculture, 2024)
Synthetic and inorganic chemical ingredients in cosmetic products pose serious health impacts on skin and hair. Much emphasis has been laid on the development of cost-effective, eco-friendly and user-friendly cosmetic products from time to time. Manufacturing cosmetics using natural ingredients is considered as a viable alternative to overcome the side effects of synthetics. Silk is a natural biopolymer obtained from cocoons of sericigenous insects like silkworms. It constitutes two proteins, viz., fibroin and sericin. Fibroin is the central core protein glued with sericin protein forming silken cocoons together. Both the proteins possess remarkable attributes viz, anti-microbial, anti-oxidant, anti-tyrosinase activity, efficient UV resistance, kinase activity, excellent release and absorption of moisture. The silk protein attributes are advantageous for body skin, hair and nails. It possesses a wide range of cosmetic applications such as facilitation of hair growth, improvement in softening and lustre of hair, rejuvenation of body and skin cells, UVB protection, prevention of chapping and brittleness of nails, and skin brightening. Due to its low molecular weight, easily penetrates the hair strands and skin cells, binds the keratin in hair and forms a protective layer to prevent moisture loss. A wide range of products have been developed for use in cosmetics viz., SILKPRO, SILKALL, SILKPRO 1000. These products are used as natural ingredients due to their potent applications in cosmetics. The cosmetic industry can be developed by proper utilization of silk in its organic products while promoting value addition to sericulture industry.